The Feasibility of E-LKPD Based on a Constructivist Approach in Physics Learning for Phase F Students on Dynamic Electricity Material - Ino Angga Putra; Jefry Ebwantoro; Suci Prihatiningtyas; Novia Ayu Sekar Pertiwi; Kartika Wulandari (APPLICATION: Applied science in Learning Research, 2025)
This study aims to determine the feasibility of E-LKPD based on a constructivist approach to the dynamic electricity material for Phase F students. This study is a type of R&D (Research and Development) research with a 4D Development Model (Define, Design, Develop, and Disseminate). This study has research limitations where researchers only carry out 3 stages without the disseminate stage due to limited time and energy. This study uses trial subjects, namely validators (validating the product) and students (product response test). The validators are carried out by two lecturers and 1 teacher who act as media experts and material experts. The product response test to assess the readability of the product was carried out by 20 students of grade XI of SMA Negeri Mojoagung Jombang. The research instruments used are: a) media expert validation sheet, b) material expert validation sheet, and c) student response questionnaire. The validation results from media experts show that the feasibility level is very feasible with an average percentage of 84%. Validation by material experts gives a feasibility value of 71%, which means it is suitable for use. Student responses to the E-LKPD were very positive, with an average percentage of 88%, indicating that this medium is interesting, easy to understand, and helpful in the learning process. The E-LKPD based on a constructivist approach is suitable for use as a supporting medium for physics learning on dynamic electricity material to improve student learning outcomes and skills.